Equivalences between 2D dilaton gravities, their asymptotic symmetries, and their holographic duals - Florian Ecker; Daniel Grumiller; Carlos Valcárcel; Dmitri Vassilevich (Journal of High Energy Physics, 2023)
Abstract Dilaton gravities in two dimensions can be formulated as particular Poisson sigma models. Target space diffeomorphisms map different models to each other and establish a one-to-one correspondence between their classical solutions. We obtain a general form of such diffeomorphisms in Lorentzian and Euclidean signatures and use them to extend known holographic results, including the Schwarzian action on the asymptotic boundary, from JT to a large class of dilaton gravity models.